دور الخدمات المصرفية الالكترونية في زيادة مستوى رضا العملاء (دراسة ميدانية على المصرف التجاري السوري- فرع اللاذقية) - هرمز نور الدين; قاسم سامر; سلمان غيداء (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يهدف البحث إلى معرفة دور الخدمات المصرفية الالكترونية المقدمة من قبل المصرف التجاري السوري في زيادة رضا العملاء, وكذلك التركيز على رضا العميل لما له من أهمية ودور في تحقيق الميزة التنافسية في تقديم الخدمات في قطاع المصارف والذي يمثل مجالاً للمنافسة بين المصارف, وبيان مدى مشاركة عاملي المصرف محل الدراسة في حرصهم على تحقيق رضا العملاء. وقدم البحث في النهاية ملخصاً لأهم النتائج التي توصل إليها, كما قدم بعض المقترحات والتوصيات التي من شأنها تحسين مستوى الخدمات المصرفية الالكترونية وتحقيق رضا العملاء بها, من خلال الدراسة الميدانية مستخدماً استبانة تم تصميمها لهذا الغرض. The research aims at finding out the role of the electronic banking services provided by the Commercial Bank of Syria in increasing customers’ satisfaction, as well as focusing on customers’ satisfaction because of its importance and its role in achieving the competitive advantage in the delivery of services in the banking sector, which represents an area of competition between public banks and private banks. Also, it aims at stating the extent of the employees’ participation in the bank under study regarding their eagerness to achieve customers’ satisfaction. At the end, the research presents a summary of the most important findings. It also presents some proposals and recommendations that will further improve the level of electronic banking services and achieving customers’ satisfaction inorder to compete at a global level through a field study using a questionnaire designed for this purpose.